Specific leaf area and photosynthetic parameters of tree species in the forest understorey as a function of the microsite light environment in central amazonia - Marenco, Ricardo Antonio; Vieira, Gil (Journal of Tropical Forest Science, 2005)
The effect of the microsite light environment (MLE) on specific leaf area (SLA), light-saturated photosynthesis (Amax), maximum transpiration (Emax) and stomatal conductance (gs-max) was examined in three tree forest species (late successional Minquartia guianensis and Scleronema micranthum, and Goupia glabra, a pioneer species) growing in the forest understorey. Logging of large trees 15 years ago had no significant effect on either SLA or photosynthetic parameters. On a per area basis, species did not differ in gas exchange parameters. However, when photosynthesis was expressed on a per mass basis (μg C g-1 DM s-1), higher photosynthetic rates were observed in Goupia (1.07) than in Scleronema (0.71) or Minquartia (0.57). SLA (m2 kg-1) was greater in Goupia (24.4) than in Scleronema (18) or Minquartia (15.9). Amax, Emax and gs-max increased as the MLE in the understorey became brighter, particularly in Goupia. Leaf respiration in the light (0.2 μmol m-2 s-1) and the apparent quantum yield (33 mmol CO2 mol-1 photon) were similar in all examined species. Regardless of logging disturbance, examined species acclimated to the MLE according to their successional status. Goupia, but not Minquartia or Scleronema, responded to its light environment mainly by changing SLA, indicating that physiological processes are involved in the acclimation of late successional species to the forest understorey.
Keywords: Photosynthesis; Transpiration; Diffuse Light; Leaf Respiration; Minquartia Guianensis; Stomatal Conductance; Forestry; Foliar Analysis; Goupia; Minquartia; Selective Cutting; Goupia; Goupia Glabra; Minquartia; Minquartia Guianensis; Scleronema; Scleronema Micranthum